2016
DOI: 10.1183/13993003.00235-2016
|View full text |Cite
|
Sign up to set email alerts
|

Annual risk of tuberculosis infection in rural China: a population-based prospective study

Abstract: Prospective population data on the incidence of tuberculosis (TB) infection has been sparsely reported in the global literature.A population-based prospective study was conducted in rural China to investigate the annual risk of TB infection, and its persistence using serial tuberculin skin tests (TSTs) and an interferon-γ release assay. In total, 13 580 eligible participants from four rural sites, identified as TST negative (<10 mm) or QuantiFERON-TB Gold In-Tube (QFT) (an interferon-γ release assay) negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 19 publications
0
24
2
Order By: Relevance
“…In prior work from our province, we have shown that the prevalence of nontuberculous Mycobacterium is high . This is likely also influential to the poor test concordance that we see in this study . Although our results show a relationship between diabetes and QFT positivity, the same association is not present with diabetes and tuberculin positivity.…”
Section: Discussioncontrasting
confidence: 76%
“…In prior work from our province, we have shown that the prevalence of nontuberculous Mycobacterium is high . This is likely also influential to the poor test concordance that we see in this study . Although our results show a relationship between diabetes and QFT positivity, the same association is not present with diabetes and tuberculin positivity.…”
Section: Discussioncontrasting
confidence: 76%
“…In our previously published study addressing in TB infection in rural China 14, 15 , the age and gender standardized prevalence of QFT positivity was found to be ranged from 13.5% to 19.8% in the selected study sites with various TB epidemic. However, it only included the registered residents with continuous residence at the study site for ≥6 months over the past year before survey.…”
Section: Discussionmentioning
confidence: 85%
“…It is consistent with the fact that the burden of TB was increasing from East China to West China 21, 22 . Considering TB prevalence in rural areas in China was approximately twice as high as it in urban areas and Shenzhen city locates in the area with low prevalence of TB 15 , it is not surprising that the higher prevalence of TB infection and of active disease among rural labor migrants might influence TB epidemic in local residents 23 . As compared to those residents continuously living in rural areas, we do not know whether the changed living conditions of rural labor migrants would change their risk of disease developing from infection 24, 25 .…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, for example, the annual risk of infection due to M. tuberculosis has been estimated to decrease from 4% in 1947 to 0.05% in 2000s . In other countries with medium risks of transmission of M. tuberculosis , the corresponding risks have been estimated to be around 1.5% to 2% in recent years. Although the generation or cohort effect is an important epidemiological mechanism driving the change in age pattern of TB with time, deviations from the cohort models have also been observed …”
Section: Epidemiology Of Tb In Older Peoplementioning
confidence: 99%